Engaging the Tanzanian diaspora in national development: What do we know and what are the gaps? - Utouh, Harold L.M.; Mutalemwa, Darlene K. (African Journal of Economic Review, 2024)
Over the past ten years, there has been a significant change in African governments’ perception of their diasporas. In the previous three decades, diasporas were not seen as a resource that countries of origin could tap into for their development needs. This is no longer the case. Now, diasporas are increasingly seen as positive actors: as countrymen and women abroad who can contribute to development efforts in their homelands. In this context, this paper reviews the literature on the major policies and initiatives used by countries to help support and promote diaspora engagement. To be specific, countries which have successfully engaged their diaspora in the national development process. The paper also highlights key factors of the success of Tanzania’s neighbouring countries and other countries. It attempts to relate these practices to the case of Tanzania, given the current social, economic, political and cultural contexts. The Tanzanian experience reveals a wide range of interventions taken to facilitate participation by its diaspora in national growth efforts. While these interventions are highly laudable- especially considering financial limits - there remain important weaknesses. Suggestions to improve existing measures are provided